A Partial Defense of Permissivism. (16th July 2015) - Sharadin, Nathaniel
Abstract: Permissivism is the view that sometimes an agent's total evidential state entails both that she is epistemically permitted to believe that P and that she is epistemically permitted to believe that Q, where P and Q are contradictories. Uniqueness is the denial of Permissivism. Permissivism has recently come under attack on several fronts. If these attacks are successful, then we may be forced to accept an unwelcome asymmetry between epistemic and practical rationality. In this essay I clarify the debate by distinguishing two versions (each) of Permissiveness and Uniqueness. I then respond to several recent challenges to Permissivism in an attempt to even the score between Permissivism and Uniqueness. I will also respond to a worry – arising out of my discussion – that a defense of Permissivism itself introduces an unwelcome asymmetry between epistemic and practical rationality.